Preparation of Investment Opportunity Map for Halal Tourism Sector (Juridical Analysis: Suraya Likupang Beach Study) - Sawitri Yuli Hartati S; Tubagus Heru Dharma Wijaya (Warmadewa Press, 2022)
The target and area to be achieved for the juridical analysis of the investment opportunity map for the halal tourism sector is the availability of a Juridical Analysis document for the preparation of a strategic priority investment opportunity map that is ready to be offered in the tourism sector which provides a comprehensive and detailed description (pre-feasibility study/pre-Feasibility Study) to investors and related stakeholders regarding the feasibility of an investment. Analyzing the feasibility of investment in the regional development sector, industry integrated with the region, and regional supporting infrastructure that will be encouraged and developed by the Government in the next 5 (five) years, taking into account the competitive advantages and comparative advantages of each region (province) in order to support equitable distribution economy to all competitive regions. Formulate proposed policy recommendations and special incentives to related Ministries/Institutions for the development of investment in strategic priority projects in the regional development sector, industry integrated with the region, and regional supporting infrastructure in Indonesia. Prepare spatial-based strategic priority project information (Geographical Information System) that is ready to be offered to investors and other related information/content that is integrated with the information system already available at BKPM. This document will become material that can be used by the Central Government and the relevant Regional Governments in offering investment projects that are truly ready to potential investors as a reliable reference in regional development, industry integrated with the region, and supporting infrastructure for Halal Tourism Areas.